Aggressive intraoperative warming versus routine thermal management during non-cardiac surgery (PROTECT): a multicentre, parallel group, superiority trial. Issue 10337 (7th May 2022) - Sessler, Daniel I; Pei, Lijian; Li, Kai; Cui, Shusen; Chan, Matthew T V; Huang, Yuguang; Wu, Jingxiang; He, Xuemei; Bajracharya, Gausan R; Rivas, Eva; Lam, Carmen K M; ,; et al.
Summary: Background: Moderate intraoperative hypothermia promotes myocardial injury, surgical site infections, and blood loss. Whether aggressive warming to a truly normothermic temperature near 37°C improves outcomes remains unknown. We aimed to test the hypothesis that aggressive intraoperative warming reduces major perioperative complications. Methods: In this multicentre, parallel group, superiority trial, patients at 12 sites in China and at the Cleveland Clinic in the USA were randomly assigned (1:1) to receive either aggressive warming to a target core temperature of 37°C (aggressively warmed group) or routine thermal management to a target of 35·5°C (routine thermal management group) during non-cardiac surgery. Randomisation was stratified by site, with computer-generated, randomly sized blocks. Eligible patients (aged ≥45 years) had at least one cardiovascular risk factor, were scheduled for inpatient non-cardiac surgery expected to last 2–6 h with general anaesthesia, and were expected to have at least half of the anterior skin surface available for warming. Patients requiring dialysis and those with a body-mass index exceeding 30 kg/m 2 were excluded. The primary outcome was a composite of myocardial injury (troponin elevation, apparently of ischaemic origin), non-fatal cardiac arrest, and all-cause mortality within 30 days of surgery, as assessed in the modified intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT03111875 . Findings: Between March 27, 2017, and March 16, 2021, 5056 participants were enrolled, of whom 5013 were included in the intention-to-treat population (2507 in the aggressively warmed group and 2506 in the routine thermal management group). Patients assigned to aggressive warming had a mean final intraoperative core temperature of 37·1°C (SD 0·3) whereas the routine thermal management group averaged 35·6°C (SD 0·3). At least one of the primary outcome components (myocardial injury after non-cardiac surgery, cardiac arrest, or mortality) occurred in 246 (9·9%) of 2497 patients in the aggressively warmed group and in 239 (9·6%) of 2490 patients in the routine thermal management group. The common effect relative risk of aggressive versus routine thermal management was an estimated 1·04 (95% CI 0·87–1·24, p=0·69). There were 39 adverse events in patients assigned to aggressive warming (17 of which were serious) and 54 in those assigned to routine thermal management (30 of which were serious). One serious adverse event, in an aggressively warmed patient, was deemed to be possibly related to thermal management. Interpretation: The incidence of a 30-day composite of major cardiovascular outcomes did not differ significantly in patients randomised to 35·5°C and to 37°C. At least over a 1·5°C range from very mild hypothermia to full normothermia, there was no evidence that any substantive outcome varied. Keeping core temperature at least 35·5°C in surgical patients appears sufficient. Funding: 3M and the Health and Medical Research Fund, Food and Health Bureau, Hong Kong. Translation: For the Chinese translation of the abstract see Supplementary Materials section.